Czy archeologia potrzebuje sztuki? Jak teoretyczne spojrzenie otwiera nowe możliwości współpracy. Sztuka jako użytkowanie - Ryczek, Justyna (Folia Praehistorica Posnaniensia, 2019)
In the following paper, a question was asked if archaeology needs art, precisely – in what way is this art needed? The author determines the value of the artistic act since we want to participate in this experiencing and even co-create this experience. Another issue is what we have from the contact with the art. The art is treated as continuously changing which imposes the transformations in the definition. The answer points out the proper understanding of the art functions, which is as using. It is significant when indicating various connections and transfers between art and other academic disciplines. It helps to notice mutual connections and relations, also with archaeology.